Mesenchymal stem cell-derived exosomes as new tools for delivery of miRNAs in the treatment of cancer - Dalmizrak, Aysegul; Dalmizrak, Ozlem (Frontiers in Bioengineering and Biotechnology, 2022)
Although ongoing medical research is working to find a cure for a variety of cancers, it continues to be one of the major causes of death worldwide. Chemotherapy and immunotherapy, as well as surgical intervention and radiation therapy, are critical components of cancer treatment. Most anti-cancer drugs are given systemically and distribute not just to tumor tissues but also to normal tissues, where they may cause side effects. Furthermore, because anti-cancer drugs have a low delivery efficiency, some tumors do not respond to them. As a result, tumor-targeted drug delivery is critical for improving the safety and efficacy of anti-cancer treatment. Exosomes are microscopic extracellular vesicles that cells produce to communicate with one another. MicroRNA (miRNA), long non-coding RNA (lncRNA), small interfering RNA (siRNA), DNA, protein, and lipids are among the therapeutic cargos found in exosomes. Recently, several studies have focused on miRNAs as a potential therapeutic element for the treatment of cancer. Mesenchymal stem cells (MSC) have been known to have angiogenic, anti-apoptotic, anti-inflammatory and immunomodulatory effects. Exosomes derived from MSCs are gaining popularity as a non-cellular alternative to MSC-based therapy, as this method avoids unwanted lineage differentiation. Therefore more research have focused on transferring miRNAs to mesenchymal stem cells (MSC) and targeting miRNA-loaded exosomes to cancer cells. Here, we initially gave an overview of the characteristics and potentials of MSC as well as the use of MSC-derived exosomes in cancer therapy. Finally, we emphasized the utilization of MSC-derived exosomes for miRNA delivery in the treatment of cancer.